Effects of bismuth additions on mechanical property and microstructure of SAC-Bi solder joint under current stressing. (February 2021) - Hu, Siou-Han; Lin, Ting-Chun; Kao, Chin-Li; Huang, Fei-Ya; Tsai, Yi-Yun; Hsiao, Shih-Chieh; Kuo, Jui-Chao
Abstract: Bi additions have been reported to improve the wettability and drop-impact performance. Most important of all, it improves the mechanical properties. However, few studies focus on the effect of the Bi addition on mechanical properties and microstructure of intermetallic compounds (IMCs) in solder balls, especially on those properties after current stressing. In this study, to understand the effect of Bi addition, a lead-free Sn-3Ag-0.5Cu-xBi (SAC305-Bi) solder joint with Bi additions from 1 to 3 wt% was used to investigate mechanical property of Sn-rich matrix and microstructure of IMCs in the solder joint after current stressing process. We combined nanoindentation, scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDS) and electron backscatter diffraction (EBSD) to analyze mechanical property, and observe the intermetallic compounds of Cu3 Sn, and Cu6 Sn5 at the interface. The mechanical properties of hardness in Sn matrix is improved by the amount of Bi, where the hardness increases from 0.095 to 0.141 GPa as increasing Bi addition from 1 to 3 wt%. In addition, the growth rate constant of intermetallic compounds of Cu3 Sn is in the range between 0.175 and 0.256, that is, Cu3 Sn is not sensitive to Bi addition. Furthermore, the amount of doping Bi addition enhances the growth rate Cu6 Sn5, as the rate constant increases from 1.597 to 2.413 with increasing Bi addition from 1 to 3 wt%. Highlights: The hardness of SAC305 solders with different bismuth additions before and after current stressing were investigated. The IMCs in the SAC305 solder with bismuth additions were identified. The microstructure evolution and growth rates of IMC in SAC305 solders with bismuth addition were analyzed and discussed.